Optimal design of a single-slotted permanent-magnet linear generator for wave energy conversion - Abdalla, I.I. (IOS Press, 2017)
As compared to other renewable energy technologies, the ocean waves are huge, largely untapped energy resource, and the potential in extracting energy is considerable. There is a lack of convergence on the best method of extracting energy from the waves, despite previous innovations, which has generally focused on the concept and design of the wave energy converter (WEC) technology, making the strategies for enhancing the efficiency of WECs important. This paper presents the performance analysis and design optimization of a single-slotted permanent-magnet linear generator. The magnetic field distribution in a cylindrical coordinate has been established. The magnetic field provides a prediction for the thrust force, flux-linkage and back-electromotive force (B-EMF), and also facilitates the characterization of the proposed machine as well as provides a basis for design optimization and dynamic modeling of the system. Finite Element Analysis (FEA) has been used for the design optimization of the proposed generator. The proposed generator has been optimized with respect to the leading design parameters Rm/Re and Tm r/TP. Thus, from the results, it can be observed that the generator has a very good efficiency to serve as WEC. ©2018 - IOS Press and the authors. All rights reserved.